2021
DOI: 10.1016/j.sjbs.2021.07.085
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of CCND1 protein and circulatory antioxidant enzyme activity association in oral squamous cell carcinoma

Abstract: Antioxidants are involved in the process of cellular damage prevention, which is considered as an avenue for cancer development. Free radicals are produced in the body upon exposure to stress, cigarette smoke, alcohol, toxins found in personal care products, pesticides in foods, radiation from the sun, viruses, germs or fungi etc. CCND1/CyclinD1 protein was found to be overexpressed in Oral squamous cell carcinoma. One hundred patients with oral squamous cell carcinoma were recruited along with hundred control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The selected studies were conducted in several nations, including IndiaClick or tap here to enter text [16-22, 24, 26-28, 30-34, 37-45, 47, 49-51, 53], Italy [23], Australia [25], Pakistan [35,48], China [36], Poland [29,52], and Saudi Arabia [46,54].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The selected studies were conducted in several nations, including IndiaClick or tap here to enter text [16-22, 24, 26-28, 30-34, 37-45, 47, 49-51, 53], Italy [23], Australia [25], Pakistan [35,48], China [36], Poland [29,52], and Saudi Arabia [46,54].…”
Section: Resultsmentioning
confidence: 99%
“…Rasheed et al[25] Patel et al[26] Raghavendra et al[27] Gokul et al[28] Giebułtowicz et al[29] Srivastava K et al[30] Gurudath et al[31] Shilpasree et al[32] Shetty et al[33] Bagul[34] Rasool et al[35] Huo et al[36] Shetty et al[37] Manasavena et al[38] Singh et al[39] Ganjre and Bagul[40] Rai et al[41] Thomas and Sethupathy[42] Shankarram et al[43] Mishra et al[44] Nyamathi et al[45] Srivastava K et al[46] Banerjee et al[47] Khan et al[48] Sadaksharam[49] Subash et al[50] Basu and Guhan[51] Babiuch et al[52] Shahi et al[53] Sushma et al[54] …”
mentioning
confidence: 99%
“… 21 , 22 , 23 , 24 , 27 , 28 , 32 , 33 , 36 , 38 , 41 , 47 Out of the four included studies that analyzed the GPx activity in blood samples except one, 48 the remaining studies displayed diminished enzyme activity in the OSCC group compared to healthy controls ( p < .05). 26 , 30 , 35 In consideration of serum samples, three studies displayed reduced activity, 25 , 37 , 51 and the remaining two depicted enhanced GPx activity in the cancerous group compared to the normal control group ( p < .05). 34 , 45 When considering GPx values in salivary samples, two studies displayed intensified activity ( p < .05) 39 , 49 ; however, one research depicted an insignificant reduction of the GPx activity.…”
Section: Discussionmentioning
confidence: 99%
“…As a key enzyme regulating ferroptosis, GPx4 can inhibit the occurrence of ferroptosis by catalyzing the reduction of lipid peroxides ( Xuan et al, 2021 ). Patients with OC have markedly low levels of superoxide dismutase, GSH peroxidase, and GSH transferase ( Sushma et al, 2021 ). An in vitro study demonstrated that enhanced intracellular GSH activity induced by natural compounds might have anti-oral cancer action by modulating oxidative stress, autophagy, and cell death ( Contant et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%